Gilgamesh is required for the maintenance of germline stem cells in Drosophila testis - Dongsheng Chen (Nature Portfolio, 2017)
Abstract Emerging evidence supports that stem cells are regulated by both intrinsic and extrinsic mechanisms. However, factors that determine the fate of stem cells remain incompletely understood. The Drosophila testis provides an exclusive powerful model in searching for potential important regulatory factors and their underlying mechanisms for controlling the fate of germline stem cells (GSCs). In this study, we have found that Drosophila gilgamesh (gish), which encodes a homologue of human CK1-γ (casein kinase 1-gamma), is required intrinsically for GSC maintenance. Our genetic analyses indicate gish is not required for Dpp/Gbb signaling silencing of bam and is dispensable for Dpp/Gbb signaling-dependent Dad expression. Finally, we show that overexpression of gish fail to dramatically increase the number of GSCs. These findings demonstrate that gish controls the fate of GSCs in Drosophila testis by a novel Dpp/Gbb signaling-independent pathway.